Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Puskesmas Dungaliyo Kecamatan Dungaliyo Kabupaten Gorontalo - Yasin, Alda Alfianti; Tahir, Arifin; Sulila, Ismet (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to investigate the effect of service quality on patient satisfaction at Puskesmas Dungaliyo, Dungaliyo Sub-District, Gorontalo Regency. Data were collected through observation, documentation and questionnaires distributed to patients in the community of Dungaliyo Sub-District, Gorontalo Regency. Then, the data were analyzed using quantitative methods. The results showed that service quality has a significant and positive effect on patient satisfaction with a coefficient of determination of 58%, which means that service quality significantly affects patient satisfaction by 58%. At the same time, the remaining 42% is affected by other factors unrelated to the variables investigated. Therefore, it is recommended for further studies to add other independent variables which are not included in this study